Halal Assurance System (HAS) 23000 Perspective George Robert Terry - Purwanto, Hery; Ahmad Rofiq; Mashudi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
A company's success in achieving its predetermined goals is possibly resulted from its good managerial skills in planning, organizing, mobilizing, and controlling. Many companies then look for a model or system to achieve those goals. Halal Assurance System (HAS 23000) is one expert management system used as a model by many companies in implementing the halal production processes. The HAS 23000 concept certainly has the management constructions, such as management functions. This library research used a descriptive-qualitative approach. The results showed that there were 11 criteria in HAS 23000 related to the management functions based on the perspective of George Robert Terry consisting of planning function, organizing function, mobilizing function, controlling or supervising function, etc. The theoretical approach proposed by George Robert Terry on management functions was used to analyze those contained in HAS 23000 and show the novelty when compared to those conducted by the previous researchers